PELATIHAN PENINGKATAN NILAI TAMBAH PRODUK HIJAU DI KELURAHAN KERANGGAN, TANGERANG SELATAN - Nusraningrum, Dewi; Indrajaya, Sonny; Imaroh, Tukhas Shilul (Jurnal Abdi Insani, 2024)
Product quality and green product innovation determine the level of competition in small, medium, and large-scale businesses. Therefore, all manufacturers are competing to improve the products produced, including green products or environmentally friendly products which are currently a central issue for businessmen in Indonesia. The purpose of this community service is to provide training to improve the quality of green products for beginner small businessmen and experienced small business people in Keranggan Village, South Tangerang so that the products produced become the target of consumers. This activity is carried out systematically starting from planning to evaluation. Training is an important strategy to increase the added value of products, especially green products that are increasingly needed in efforts to mitigate environmental degradation. The training methods used are lectures, discussions, and surveys of the participants before and after the training.  The results of community service show that most small business owners in Keranggan have a very high need to increase the value of their products. The training covers various topics, ranging from selecting raw materials, production processes, and evaluating environmentally friendly products. The assessment of the training session showed a significant increase in participants' understanding and commitment to developing the value of the resulting green products. The practical implications of this community service include the importance of continuously strengthening the small and medium business community about green products that are competitive.